Penerapan Metode SMARTER pada Sistem Pendukung Keputusan Pemilihan Lahan Kayu Putih - Ratih Hafsarah Maharrani; Prih Diantono Abda’u; Hety Dwi Hastuti (Universitas Budi Darma, 2023)
The productivity of eucalyptus in Indonesia is included in the low productivity group, the lack of raw materials resulting in a deficit in eucalyptus production is the cause of this. Meanwhile market demand is increasing. The large area of land in the Cilacap Regency area is not matched by its utilization, this is due to a lack of knowledge about potential land uses. There are 5 criteria for land, namely land